2001
DOI: 10.1111/j.1349-7006.2001.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hepatic and Peritoneal Metastases by the Angiogenesis Inhibitor FR‐118487 after Removal of Growing Tumor in Mice

Abstract: We established a mouse "primary tumor resection model" in which a transplanted tumor was resected after an orthotopic transplantation of colorectal cancer tissue to estimate the therapeutic effect of an angiogenesis inhibitor on metastasis. The angiogenesis inhibitor FR-118487 is a member of the fumagillin family. Here, 1 mg/kg/day of FR-118487 was subcutaneously administered to nude mice for 1 week, 2 weeks, or 4 weeks through an osmotic pump. Liver metastasis developed in 7 of 9 control mice, 2 of 6 mice tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Arteries (arrow) and veins (asterisk) can be discriminated in the 3D images (c, d) [26,27,28,29,30,31]. There have been several reports on angiogenesis [25,26,27,28,29,30,31,32,33]. Folkman et al [32,33] defined angiogenesis as the formation of new blood vessels produced by the proliferation and migration of vascular endothelial cells in old blood vessels, a biological reaction which occurs under various physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Arteries (arrow) and veins (asterisk) can be discriminated in the 3D images (c, d) [26,27,28,29,30,31]. There have been several reports on angiogenesis [25,26,27,28,29,30,31,32,33]. Folkman et al [32,33] defined angiogenesis as the formation of new blood vessels produced by the proliferation and migration of vascular endothelial cells in old blood vessels, a biological reaction which occurs under various physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Images of VX2 tumors obtained by a, b soft X-ray irradiation, c micro-CT, and d rotational micro-CT. Neovascularization and tortuous vessels, not found in normal rabbits, are present in the transplantation area seen on the micro-CT images. Arteries (arrow) and veins (asterisk) can be discriminated in the 3D images (c, d) [26,27,28,29,30,31]. There have been several reports on angiogenesis [25,26,27,28,29,30,31,32,33].…”
Section: Discussionmentioning
confidence: 92%
“…Many in vivo studies have shown that VEGF also plays important roles in the development of peritoneal metastasis [3][4][5][6][7]. In accordance, malignant ascites in ovarian or gastrointestinal cancer patients contains elevated levels of VEGF [8 -11].…”
Section: Introductionmentioning
confidence: 99%
“…After 5 wk of drug administration, mice were sacrificed and tumors were removed and weighed. Metastatic foci on the liver surface were counted macroscopically and were confirmed microscopically, as reported previously (28,29).…”
Section: Animals and Tumor Modelsmentioning
confidence: 99%